Anti-ablation and thermal insulation properties of silicone rubber composites based on ceramization-carbonization mechanism - ZHANG Feng, GAO Jing-long, LIU Yan-hui (Hecheng xiangjiao gongye)
Silicone rubber composites with anti-ablation and thermal insulation properties were prepared with hot vulcanized silicone rubber as matrix, and polyarylacetylene, short carbon fiber, zirconia and carbon fiber cloth as anti-ablation fillers, and the effect of anti-ablation fillers on linear ablation rate and substrate temperature of the composites was investigated. The results showed that the linear ablation rate and substrate temperature of the composites were decreased with the sequential addition of the anti-ablation fillers. When the addition amount of polyarylacetylene, short carbon fiber, zirconia, and carbon fiber cloth were all 10 phr (mass), the resul-ting composite had the best anti-ablation and thermal insulation properties with a linear ablation rate of 0.043 mm/s and a substrate temperature of 70 ℃. This was mainly attributed to the ceramization-carbonization coupling reaction between the anti-ablation fillers and silicone rubber matrix, which led to the formation of a dense ablation layer that covered the surface of carbon fiber cloth.